2017
DOI: 10.1038/srep40796
|View full text |Cite
|
Sign up to set email alerts
|

A new type of two-dimensional carbon crystal prepared from 1,3,5-trihydroxybenzene

Abstract: A new two-dimensional (2D) carbon crystal, different from graphene, has been prepared from 1,3,5-trihydroxybenzene, consisting of 4-carbon and 6-carbon rings in 1:1 ratio, named 4-6 carbophene by authors, in which all carbon atoms possess sp 2 hybrid orbitals with some distortion, forming an extensive conjugated π-bonding planar structure. The angles between the three σ-bonds of the carbon sp 2 orbitals are roughly 120°, 90°, and 150°. Each of the three non-adjacent sides of a 6C-ring is shared with a 4C-ring;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(28 citation statements)
references
References 55 publications
(53 reference statements)
1
27
0
Order By: Relevance
“…In recent years, people found many 2D materials from allotropes of carbon and from group V elements. Some of them have potential application in optoelectronic, nano electronic devices and hydrogen storage, because of their unique electronic and mechanical properties [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In 2018, Cao et al found the twisted bilayer graphene is able to be an insulator or superconductor [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, people found many 2D materials from allotropes of carbon and from group V elements. Some of them have potential application in optoelectronic, nano electronic devices and hydrogen storage, because of their unique electronic and mechanical properties [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In 2018, Cao et al found the twisted bilayer graphene is able to be an insulator or superconductor [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of these combinations is the so called graphenylene, which has a small band gap and delocalized frontier orbitals [28][29][30]. A possible route to the synthesis of graphenylene was proposed elsewhere [28] and its experimental realization, although obtained through a different route, was reported recently [31,32]. Further, Schlütter et al reported recently that they were able to synthesize octafunctionalized biphenylene GNRs [33].…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that a carbophene would be the more likely candidate for what Du et al produced. [16,17] Du et al reported that their synthesized material contained oxygen, thus to better fit this condition, future work should replace hydrogen atoms with oxygen-containing functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…[12,16] Some of the results that Du et al reported suggest that they had not synthesized graphenylene but, instead, a 2D hydrocarbon material based on linear 3-phenylene. [17] To the best of our knowledge, no experimental followup has determined which material Du et al synthesized. Nor has the 2D hydrocarbon (denoted here as 3-carbophene) been theoretically examined before now.…”
Section: Introductionmentioning
confidence: 99%